Analisis Dan Perancangan Sistem Informasi Produksi Pada PT.Plantex Sembada International Jambi - Az-zahra', Nur Amanah; Dodo Zaenal Abidin; Joni Devitra (LPPM Universitas Dinamika Bangsa, 2024)
PT. Plantex Sembada International Jambi is a areca nut export and import company located in Jambi City. PT.Plantex Sembada International Jambi has not made full use of information and communication technology and does not have an information system that can help direct the production process, resulting in a long time in accessing the required data and information. With the production information system of PT. Plantex Sembada International Jambi can make it easier to manage production data. Object-based modeling used to describe the analysis system is UML (Unified Modeling Language) modeling in the form of use case diagrams, activity diagrams, class diagrams, and flowchart. The output of this research is a web-based Production Information System prototype design at PT. Plantex Sembada International Jambi. Production information system can reduce the time and energy required for the production process and reduce the risk of manual recording errors, manage inventory better such as the risk of exess or shortage of stock, and make it easier to create accurate and structured reports.